Muscle Ageing and Sarcopenia Study (MASS) Lifecourse: a valuable resource for understanding skeletal muscle ageing - Rachel Cooper; Christopher Hurst; Holly Syddall; Helen Atkinson; Jonathan G. Bunn; Daniela Carpinelli; Antoneta Granic; Susan J. Hillman; Emma Grace Lewis; Claire McDonald; Katie Sloan; Karen Suetterlin; et al. (GeroScience, 2026)

Evolving glacier landsystems during Patagonian Ice Sheet recession influenced by a changing topographic setting - Emma-Louise Cooper; Bethan J. Davies; Varyl.R. Thorndycraft; Adrian P. Palmer; Juan-Luis García; David J.A. Evans; Christopher Lüthgens; Andrew N. Mackintosh (Geomorphology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Can we use springtails to improve our understanding of Antarctic Ice Sheet history? — A case study from Dronning Maud Land - Emma-Louise Cooper; Mark I. Stevens; Richard S. Jones; Andrew N. Mackintosh (Quaternary Science Reviews, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Evidence of resident coastal population(s) of false killer whales (Pseudorca crassidens) in northern Australian waters - Carol Palmer; Karen K. Martien; Holly Raudino; Kelly M. Robertson; Alan Withers; Emma Withers; Robert Risk; Dylan Cooper; Ellen D’Cruz; Edmund Jungine; Daniel Barrow; Nick Cuff; et al. (Frontiers in Marine Science, 2023)
To help evaluate the distribution, residency, population size and structuring (and hence conservation status) of the poorly known false killer whale Pseudorca crassidens in northern Australian waters, we undertook studies of sightings, movement patterns based on satellite telemetry, and genetics. Sighting data indicates that false killer whales are regular, year-round inhabitants of coastal areas of northern Australia. Satellite-tagged animals spent extended periods of time in shallow coastal waters, with no tagged animals leaving the continental shelf. The lack of spatial overlap in the areas visited by individuals tagged in the Arafura/Timor Seas compared to those tagged in the Gulf of Carpentaria suggests that there may be more than one population in northern Australia coastal waters. All 14 genetic samples collected across 1600 km of coastline possessed the same newly identified mitochondrial control region haplotype, designated haplotype 45. Notably, haplotype 45 is distinct from all previously published false killer whale haplotypes globally and is most similar to the two haplotypes that typify the endangered main Hawaiian Islands insular false killer whale population. Based on these results and evidence from recent movement records of those tagged, false killer whales in northern Australia are apparently demographically independent from the offshore population(s). Further assessment of the population conservation status is now required.

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Plasma metals as potential biomarkers in dementia: a case–control study in patients with sporadic Alzheimer’s disease - Jingshu Xu; Stephanie J. Church; Stefano Patassini; Paul Begley; Katherine A. B. Kellett; Emma R. L. C. Vardy; Richard D. Unwin; Nigel M. Hooper; Garth J. S. Cooper (BioMetals, 2018)

Local genes for local bacteria: Evidence of allopatry in the genomes of transatlantic Campylobacter populations - Ben Pascoe; Guillaume Méric; Koji Yahara; Helen Wimalarathna; Susan Murray; Matthew D. Hitchings; Emma L. Sproston; Catherine D. Carrillo; Eduardo N. Taboada; Kerry K. Cooper; Steven Huynh; Alison J. Cody; et al. (Molecular Ecology, 2017)
The genetic structure of bacterial populations can be related to geographical locations of isolation. In some species, there is a strong correlation between geographical distance and genetic distance, which can be caused by different evolutionary mechanisms. Patterns of ancient admixture in Helicobacter pylori can be reconstructed in concordance with past human migration, whereas in Mycobacterium tuberculosis it is the lack of recombination that causes allopatric clusters. In Campylobacter , analyses of genomic data and molecular typing have been successful in determining the reservoir host species, but not geographical origin. We investigated biogeographical variation in highly recombining genes to determine the extent of clustering between genomes from geographically distinct Campylobacter populations. Whole‐genome sequences from 294 Campylobacter isolates from North America and the UK were analysed. Isolates from within the same country shared more recently recombined DNA than isolates from different countries. Using 15 UK /American closely matched pairs of isolates that shared ancestors, we identify regions that have frequently and recently recombined to test their correlation with geographical origin. The seven genes that demonstrated the greatest clustering by geography were used in an attribution model to infer geographical origin which was tested using a further 383 UK clinical isolates to detect signatures of recent foreign travel. Patient records indicated that in 46 cases, travel abroad had occurred UK origin. Identification of biogeographical markers in Campylobacter genomes will contribute to improved source attribution of clinical Campylobacter infection and inform intervention strategies to reduce campylobacteriosis.

Potentially inappropriate prescribing in two populations with differing socio-economic profiles: a cross-sectional database study using the PROMPT criteria - Janine A. Cooper; Frank Moriarty; Cristín Ryan; Susan M. Smith; Kathleen Bennett; Tom Fahey; Emma Wallace; Caitriona Cahir; David Williams; Mary Teeling; Carmel M. Hughes (European Journal of Clinical Pharmacology, 2016)